Harina de zanahoria blanca y de malanga como sustancias de relleno alternativas en la elaboración de mortadela tipo III - Guevara Muñoz, Jhadira Fernanda (2023)
The objective of this work was to evaluate the effect of white carrot and taro flour as an alternative to filling substances in the preparation of Type III mortadella, in the formulation of each treatment percentages 20-80, 40-60, 60- 40 and 80-20 of flours respectively with four replicates each, the experimental unit was 3 kg of mortadella to which the determination of total proteins, cooking losses, texture profile, and general acceptability of the treatments was performed, in the results achieved it was evidenced that the combination of flours had no influence on the total proteins, all the treatments exceeded the minimum 8% established in the NTE INEN 1338:2012, regarding cooking losses, all the treatments were found by below the maximum established of 65% in NTE INEN 1340:1997, regarding the texture profile, it was influenced by showing T4 as the best treatment (80% malanga flour and 20% zanahoria flour), with 46.35 N in hardness and 0.09 in adhesiveness, in terms of chewiness and elasticity the best treatment was T3 (40% taro flour and 60% white carrot flour) with 16.11 N and 0.55 respectively, finally regarding the general acceptability, the panelists did not identify differences in the parameters of color, taste and smell, concluding that white carrot and malanga flours are a convenient option to use in the elaboration of scalded products such as type III mortadella.